Literary genres in the court culture of the Elizabethan times (Literatures of the World: Poetics, Mentality and Spirituality, 2016)
The paper studies the specific development of new forms of genre in court literature of Elizabethan England. It was concluded that the process was influenced by classical heritage and literary experiments. These experiments contributed to emerging trends in productivity, originality, and new art forms.
Keywords: literary genres; court culture; Elizabethan; petrarchism; mannerism; euphuism; arcadism